Pengaruh Citra Merek Dan Harga Terhadap Keputusan Pembelian Maskara Maybelline (Studi Kasus Pada Mahasiswi Administrasi Niaga Politeknik Negeri Jakarta) - Sarah Fahira; Tuti Hartati; Hafniza Amir (Politeknik Negeri Jakarta, 2019)
Respondents in this study amounted to 80 people who were students of the Department of Commercial Administration of the Jakarta State Polytechnic who had bought Maybelline mascara. The results showed that brand image factors and prices influence the purchasing decisions of Maybelline mascara. This is evidenced by the regression coefficient of 0.503. Brand image has a positive and significant influence on purchasing decisions of Maybelline mascara with a value of 0,017 <0,10. This is because the brand image is the initial foundation of consumers to be able to choose what products to use. Prices have a positive and significant influence on consumer purchasing decisions with a value of 0.005 <0.10. This is because each consumer has a perception of a price, if the price offered is suitable then the consumer can choose the product or want to use. Brand image and price together influence the purchasing decision of Maybelline mascara with a significance value of 0,000 <0.10.